How Do Academically Selective School Systems Affect Pupils' Social-Emotional Competencies? New Evidence From the Millennium Cohort Study. (October 2019) - Jerrim, John; Sims, Sam
An extensive literature has investigated the link between living in an area with an academically selective schooling system and young people's educational outcomes. In contrast, evidence on the link between selective education and young people's wider outcomes is relatively sparse. This article uses rich survey data to test whether young people living in selective education areas in England have better academic, social, and emotional outcomes than their peers who live in nonselective areas. Results show that exposure to the selection process has limited impact upon young people's socioemotional outcomes. We do find, however, that selective systems increase the socioeconomic gradient of educational aspirations, driven by divergence between those who do and do not gain entry to the selective track.